Underfloor air distribution technology: A review - Al Sambathan S.; Ismail F.B.; Nasif M.S. (American Institute of Physics Inc., 2023)
The underfloor air system is a new concept that was introduced for its fairly exceptional advantages for its advantages in terms for design flexibility, improve indoor thermal comfort (ITC), indoor air quality (IAQ), reduces life cycle cost and energy efficient by supplying air that is conditioned to a comfortable temperature and appropriate air ventilation speed in commercial buildings and data centers. Although the system has its benefits, the reliability of the UFAD system is still limited due to lack of understanding on the thermal stratification behavior and the analysis of energy consumption which is still difficult for building designers to apply the UFAD system as a daily driver. The purpose of this paper is to review the past studies that was done on the UFAD system to determine the gaps that still exist and suggestion that can be done to facilitate further study on the system. 2018 Author(s).